Molecular tools to capture active neural circuits - Onishi, Taichi; Hirose, Kenzo; Sakaba, Takeshi (Frontiers in Neural Circuits, 2024)
To understand how neurons and neural circuits function during behaviors, it is essential to record neuronal activity in the brain in vivo. Among the various technologies developed for recording neuronal activity, molecular tools that induce gene expression in an activity-dependent manner have attracted particular attention for their ability to clarify the causal relationships between neuronal activity and behavior. In this review, we summarize recently developed activity-dependent gene expression tools and their potential contributions to the study of neural circuits.